2020
DOI: 10.7150/jca.44777
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Kif20a inhibits growth of tumors in soft tissue sarcoma in vitro and in vivo

Abstract: Kif20a (Kinesin Family Member 20A), plays a role in cell mitosis, cell migration and intracellular transport. Numerous studies have demonstrated that Kif20a is abnormally highly expressed in a variety of tumors and shows poor prognosis. Soft tissue sarcoma (STS) represents a group of malignant tumors with poor prognosis. The role of Kif20a in STSs has not been systematically studied. In the present study, bioinformatics analysis, in vitro and in vivo experiments were conducted to investigate the function of Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…KIF20A can affect the prognosis of bladder cancer by promoting the proliferation and metastasis of bladder cancer cells.KIF20A [ 22 ]. In soft tissue sarcoma, KIF20A gene knockout can inhibit the proliferation, migration and invasion of soft tissue sarcoma cells, promote cell apoptosis, and inhibit tumor growth [ 23 ]. These results indicated that KIF20A had an important effect on the proliferation, invasion and apoptosis of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…KIF20A can affect the prognosis of bladder cancer by promoting the proliferation and metastasis of bladder cancer cells.KIF20A [ 22 ]. In soft tissue sarcoma, KIF20A gene knockout can inhibit the proliferation, migration and invasion of soft tissue sarcoma cells, promote cell apoptosis, and inhibit tumor growth [ 23 ]. These results indicated that KIF20A had an important effect on the proliferation, invasion and apoptosis of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…MCA‐induced fibrosarcoma 207 is a well‐established soft tissue sarcoma model that is used to study tumour regression and immunity in C57BL/6 mice. 11 , 12 [ S3 ] Continuous passaging of MCA207 cells caused a ‘drift’ in tumour phenotype and cachexia in CHX207‐tumour‐bearing mice. Intramuscular injection of MCA207‐ or CHX207 cells resulted in solid tumours, which were palpable around 7 days post injection (p.i.).…”
Section: Resultsmentioning
confidence: 99%
“…The overexpression of KIF20A is linked to the onset, progression, and prognosis of different cancers. Recent researches have reported that KIF20A was upregulated in esophageal squamous cell carcinoma ( 28 ), lung adenocarcinoma ( 29 ), prostate cancer ( 30 ), cervical cancer ( 31 ), colorectal cancer ( 32 ), non-small cell lung cancer ( 33 ), gastric cancer ( 34 ), bladder cancer ( 35 ), renal clear cell carcinoma ( 36 ), breast cancer ( 37 ), hepatocellular carcinoma ( 38 ), nasopharyngeal carcinoma ( 39 ), ovarian cancer ( 40 ), leukemia ( 25 ), glioma ( 41 ), and soft tissue sarcoma ( 42 ). This is consistent with our analysis in the GEPIA online database.…”
Section: Discussionmentioning
confidence: 99%